2013
DOI: 10.3109/15563650.2012.757318
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of magnesium sulfate in acute organophosphate pesticide poisoning

Abstract: Magnesium was well tolerated in this study. Larger studies are required to examine for efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 24 publications
3
25
0
Order By: Relevance
“…MgSO 4 at all doses was well-tolerated. [20] However, a dose of 4 g was selected for this study, keeping in mind the ease of administration and need for less intense monitoring of magnesium levels. Although an increase in serum magnesium levels was noted following the administration of MgSO 4 , it was within the therapeutic range, and none of the patients had clinical side effects attributable to magnesium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MgSO 4 at all doses was well-tolerated. [20] However, a dose of 4 g was selected for this study, keeping in mind the ease of administration and need for less intense monitoring of magnesium levels. Although an increase in serum magnesium levels was noted following the administration of MgSO 4 , it was within the therapeutic range, and none of the patients had clinical side effects attributable to magnesium.…”
Section: Discussionmentioning
confidence: 99%
“…The observations concur with that of other studies. [1920] The requirement of atropine in OPCP may vary with the severity of poisoning. [21] There is conflicting evidence regarding the effect of magnesium on atropine requirement.…”
Section: Discussionmentioning
confidence: 99%
“…Sodium bicarbonate, magnesium, and diazepam are used in human OP insecticide poisonings but have not shown overall benefit (107,111). Improved airway control during hospital transfer, by intubation or placement of supraglottic airways, could reduce pulmonary complications.…”
Section: Hours To Daysmentioning
confidence: 99%
“…Larger controlled studies should be performed to determine the efficacy of magnesium sulphate in OP poisoning. (21) LIMITATION Limitations of our study are small sample size and a further potential limitation is that we did not have the capacity to confirm exposure by analysis and identification of the specific organophosphate or by inhibition of cholinesterase. However, cohort studies in similar settings showed laboratory confirmation of agrochemicals ingestion in 95% of cases.…”
Section: Discussionmentioning
confidence: 99%